The relationship between young adult smokers' beliefs about nicotine addiction and smoking-related affect and cognitions - Waters, Erika A. (J Cancer Educ, 2016)
Risk beliefs and self-efficacy play important roles in explaining smoking-related outcomes and are important to target in tobacco control interventions. However, information is lacking about the underlying beliefs that drive these constructs. The present study investigated the interrelationships among young adult smokers' beliefs about the nature of nicotine addiction and smoking-related affect and cognitions (i.e., feelings of risk, worry about experiencing the harms of smoking, self-efficacy of quitting, and intentions to quit). Smokers (N=333) were recruited from two large universities. Results showed that quit intentions were associated with feelings of risk, but not with worry or self-efficacy. Furthermore, higher feelings of risk were associated with lower beliefs that addiction is an inevitable consequence of smoking and with lower beliefs that the harms of smoking are delayed. This suggests that it is important for health messages to counter the possible negative effects of messages that strongly emphasize the addictiveness of nicotine, possibly by emphasizing the importance of quitting earlier rather than later. The findings also add to the evidence base that feelings of risk are powerful predictors of behavioral intentions. Furthermore, our results suggest that in some circumstances, feelings of risk predict quit intentions beyond that predicted by worry and self-efficacy. Gaining additional understanding of the tobacco-related beliefs that can increase feelings of risk and incorporating those beliefs into educational campaigns may improve the quality of such campaigns and reduce tobacco use.